Proteasome Inhibitor YSY01A Abrogates Constitutive STAT3 Signaling via Down-regulation of Gp130 and JAK2 in Human A549 Lung Cancer Cells - Huang, Wei; Yuan, Xia; Sun, Ting; Fan, Shujie; Wang, Jun; Zhou, Quan; Guo, Wei; Ran, Fuxiang; Ge, Zemei; Yang, Huayu; Li, Runtao; Cui, Jingrong (Frontiers in Pharmacology, 2017)
Proteasome inhibition interfering with many cell signaling pathways has been extensively explored as a therapeutic strategy for cancers. Proteasome inhibitor YSY01A is a novel agent that has shown remarkable anti-tumor effects; however, its mechanisms of action are not fully understood. Here we report that YSY01A is capable of suppressing cancer cell survival by induction of apoptosis. Paradoxically, we find that YSY01A abrogates constitutive activation of STAT3 via proteasome-independent degradation of gp130 and JAK2, but not transcriptional regulation, in human A549 non-small cell lung cancer cells. The reduction in gp130 and JAK2 can be restored by co-treatment with 3-methyladenine, an early-stage autophagy lysosome and type I/III PI3K inhibitor. YSY01A also effectively inhibits cancer cell migration and lung xenograft tumor growth with little adverse effect on animals. Thus our findings suggest that YSY01A represents a promising candidate for further development of novel anticancer therapeutics targeting the proteasome.